Fred E. Inbau: 'The Importance of Being Guilty' - Kamisar, Yale (1977)
As fate would have it, Fred Inbau graduated from law school in 1932, the very year that, for practical purposes the modern law of constitutional criminal procedure [began], with the decision in the great case of Powell v. Alabama. 1 In the 'stone age' of American criminal procedure, 2 Inbau began his long fight to shape or to retain rules that make sense in the light of a policeman's task, 3 more aware than most that so long as the rules do so, we will be in a stronger position to insist that [the officer] obey them.